2018
DOI: 10.2147/jpr.s151562
|View full text |Cite
|
Sign up to set email alerts
|

Altered low-frequency oscillation amplitude of resting state-fMRI in patients with discogenic low-back and leg pain

Abstract: ObjectiveThe aim of this study was to explore the amplitude of intrinsic low-frequency oscillations (LFOs) in patients with discogenic low-back and leg pain (LBLP).Participants and methodsWe obtained and compared the LFO amplitude from 25 right-handed discogenic LBLP patients (13 males; mean age 55.16±1.83 years) and 27 well-matched healthy controls (15 males; mean age 52.96±1.63 years). The LFO amplitude was examined using the voxel-wise amplitude of low-frequency fluctuations (ALFFs), and partial correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 50 publications
6
45
3
Order By: Relevance
“…A study suggested that patients with blindness had changes in the thickness of the middle occipital gyrus [47]. Another study reported that patients with discogenic low back and leg pain showed increased ALFF in the left middle occipital gyrus [16]. However, our study had inconsistent findings for this region.…”
Section: Occipital Regioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A study suggested that patients with blindness had changes in the thickness of the middle occipital gyrus [47]. Another study reported that patients with discogenic low back and leg pain showed increased ALFF in the left middle occipital gyrus [16]. However, our study had inconsistent findings for this region.…”
Section: Occipital Regioncontrasting
confidence: 70%
“…Resting-state functional magnetic resonance imaging (rs-fMRI), widely used in chronic pain diseases [11][12][13][14][15], is an effective tool to evaluate the intrinsic neural activity of the human brain [16,17]. The rs-fMRI analysis methods mainly include amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo) [9], and functional connectivity (FC) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Functional connectivity results suggest that, as pain becomes chronic (i.e., >1 y), the NAc subcircuitries fc show dynamic changes. We therefore studied power spectral density (PSD) (20, 21) because this approach uncovered meaningful differences among clinical populations (22) including chronic pain patients (23)(24)(25)(26)(27)(28)(29). We calculated PSD for different frequency bands defined in previous neurophysiological and fMRI studies (21,30,31) in bilateral NAc and compared among groups using a hypothesis-based approach.…”
Section: Sbpp and Sbpr Show Differences In Corticostriatal Functionalmentioning
confidence: 99%
“…The thalamus, on the other hand, has an important function in pain perception as a target of ascending spinal activity and some studies indicate altered functioning (Fenton et al, 2015). Zhou et al (2018) reported a decrease in ALFF in the thalamus in discogenic low back and leg pain patients, while an increase in ALFF in the thalamus was observed after pain‐exacerbating maneuvers in chronic low back pain patients (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing body of research shows altered intrinsic neural activity in chronic pain (Alshelh et al, 2017; Baliki & Apkarian, 2015; Zhang et al, 2019). In addition, Zhou et al (2018) reported increased amplitude of low‐frequency fluctuations (ALFF) in regions of the pain matrix such as anterior insula or orbitofrontal cortex, as well as decreased ALFF in basal ganglia, thalamus and midbrain in patients with discogenic low‐back and leg pain. It is noteworthy that several other studies have shown disrupted functional connectivity in patients with chronic back pain, particularly in cortical midline regions (i.e., medial prefrontal cortex, cingulate cortex, amygdala and insula (Kregel et al, 2015; Tagliazucchi, Balenzuela, Fraiman, & Chialvo, 2010).…”
Section: Introductionmentioning
confidence: 99%